Farmer Participatory Seed Potato Production through Krishi Vigyn kandra Networking: An action research for enhancing availability of seed in the country - singh, Rajesh kumar (Potato Journal, 2017)
Use of poor potato seed quality has been envisaged as one of major causes of low productivity in India. Keeping these facts under consideration, a participatory trial on â€œSeed Plot Techniqueâ€ was taken up at five locations in the district of Lucknow, Uttar Pradesh, India with a small group of farmers taking potato cultivation as cash crop. The complete package of seed plot techniques was assessed and capacity building interventions were also implemented. Performance of this technique was compared with the conventional practices of seed potato production. Technical and socio-psychological impact as well as the sustainability of this technique was ascertained on the established indicators. Results showed that Seed Plot Technique was highly effective as it reduced the aphid population by 74.1%, white fly population by 86.9%, and mosaic incidence by 75.8.0%, besides, achievingÂ bumper crop yield (with an increase of 16.3%). The techniques was recorded as cost effective (a higher B: C ratio of 2.6) and sustainable (score 80) over the conventional system (B: C ratio=2.0; score 53). Findings have wider implication for establishment of replicable and remunerative agri-business model of commercial seed potato production in plains of Uttar Pradesh using the innovative seed plot technique.Â